Fast and simple method for identification of adulteration of cow's milk with urea using diffuse reflectance spectroscopy - Toledo, Paulo R. A. B. de [UNESP]; Toci, Aline T.; Pezza, Helena R. [UNESP]; Pezza, Leonardo [UNESP] (Royal Soc Chemistry, 2017)
This work describes the development and application of a simple, fast, cheap, and clean method for the detection of adulteration of raw cow's milk by urea, using a combined spot test/diffuse reflectance spectroscopy procedure. The proposed method is based on the reaction of urea with a chromogenic reagent, p-dimethylaminobenzaldehyde (p-DAB) in acidified methanol, yielding a colored compound on the surface of a filter paper. The reaction parameters were optimized using chemometric experimental design. Reflectometric measurements of the colored product were carried out at 440 nm. The linear range was from 25 to 750 mg L-1 (R = 0.992). The proposed method was successfully applied in the analysis of urea in cow's milk samples, demonstrating that it is a reliable alternative method for the screening and detection of urea in cow's milk.